New Paradigm in Millennial Business: A Case Study of Pilona Coffee, Tangerang City - Tri Anggreni; Canggih Gumanky Farunik; Hendra Hendra (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
Millennial has its own character of thinking, because when compared to the previous generation who carried out the process of adaptation to the development of information technology, millennial grew and lived with the technology. They thrive with memes, digital markets, electronic money, and social media networks. Virality makes something quickly famous and quickly forgotten, collective memory is limited to how long digital traces can last on the internet. On the basis of that problem, this study was prepared with the question "What is the character of millennial leadership based on the organizational culture of the natural ecosystems they have built?” The purpose of this study is to understand the cultural character of millennial organizations based on their natural ecosystem so that they influence the lead character. This study uses a qualitative method with close observation within a certain period of time for several millennial adolescents involved in the organization as the main sample, categorized based on their level of exposure to the internet. The expected outcome of this research is a deep understanding of how millennial organizational culture influences the character of its leadership.